The Presidential Pulse of Congressional Elections - Campbell, James E., 1952- (Book collections on Project MUSE., 2015)
An intriguing phenomenon in American electoral politics is the loss of seats by the president's party in midterm congressional elections. Between 1862 and 1990, the president's party lost seats in the House of Representatives in 32 of the 33 midterm elections. In his new study, James Campbell examines explanations for these midterm losses and explores how presidential elections influence congressional elections. After reviewing the two major theories of midterm electoral change-the ""surge and decline"" theory and the theory of midterms as referenda on presidential performance Campbell draws up.